Role of adenosine A2a receptor in cancers and autoimmune diseases - Hongling Ye; Junqi Zhao; Xuejing Xu; Dagan Zhang; Han Shen; Sen Wang (Immunity, Inflammation and Disease)
Abstract Adenosine receptors are P1 class of purinergic receptors that belong to G protein‐coupled receptors. There are 4 subtypes of adenosine receptors, namely A1, A2A, A2B, and A3. A2AR has a high affinity for the ligand adenosine. Under pathological conditions or external stimuli, ATP is sequentially hydrolyzed to adenosine by CD39 and CD73. The combination of adenosine and A2AR can increase the concentration of cAMP and activate a series of downstream signaling pathways, and further playing the role of immunosuppression and promotion of tumor invasion. A2AR is expressed to some extent on various immune cells, where it is abnormally expressed on immune cells in cancers and autoimmune diseases. A2AR expression also correlates with disease progression. Inhibitors and agonists of A2AR may be potential new strategies for treatment of cancers and autoimmune diseases. We herein briefly reviewed the expression and distribution of A2AR, adenosine/A2AR signaling pathway, expression, and potential as a therapeutic target.